2015
DOI: 10.1007/s00253-015-7147-3
|View full text |Cite
|
Sign up to set email alerts
|

A synergistic interaction between salt-tolerant Pseudomonas and Mesorhizobium strains improves growth and symbiotic performance of liquorice (Glycyrrhiza uralensis Fish.) under salt stress

Abstract: Chinese liquorice (Glycyrrhiza uralensis Fish.) is a salt-tolerant medicinal legume that could be utilized for bioremediation of salt-affected soils. We studied whether co-inoculation of the symbiotic Mesorhizobium sp. strain NWXJ19 or NWXJ31 with the plant growth-promoting Pseudomonas extremorientalis TSAU20 could restore growth, nodulation, and shoot/root nitrogen contents of salt-stressed G. uralensis, which was grown in potting soil and irrigated with 0, 50, and 75 mM NaCl solutions under greenhouse condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 39 publications
2
51
0
2
Order By: Relevance
“…However, the selection rationale of host plants, locations, and pretreatment methods for the isolation of endophytes is essential in biodiversity research (Strobel and Daisy, 2003;Zhang et al, 2016). Besides, endophytic resources of arid land are most likely to possess unique and diverse functions, such as degrading chitin, producing siderophore, encoding antimicrobial and antibiotic biosynthetic genes, because of their high ability to adapt the extremely arid environment (Qin et al, 2009;Cho et al, 2015;Egamberdieva et al, 2016Egamberdieva et al, , 2017cLi et al, 2018). For instance, our research group reported that the vast majority of endophytic isolates from Chinese traditional medicinal plants Ferula sinkiangensis, Glycyrrhiza uralensis, and Ferula songorica in Xinjiang arid land were capable of producing both antifungal and plant growth-promoting traits (Liu et al, 2016(Liu et al, , 2017Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the selection rationale of host plants, locations, and pretreatment methods for the isolation of endophytes is essential in biodiversity research (Strobel and Daisy, 2003;Zhang et al, 2016). Besides, endophytic resources of arid land are most likely to possess unique and diverse functions, such as degrading chitin, producing siderophore, encoding antimicrobial and antibiotic biosynthetic genes, because of their high ability to adapt the extremely arid environment (Qin et al, 2009;Cho et al, 2015;Egamberdieva et al, 2016Egamberdieva et al, , 2017cLi et al, 2018). For instance, our research group reported that the vast majority of endophytic isolates from Chinese traditional medicinal plants Ferula sinkiangensis, Glycyrrhiza uralensis, and Ferula songorica in Xinjiang arid land were capable of producing both antifungal and plant growth-promoting traits (Liu et al, 2016(Liu et al, , 2017Li et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…is a very popular herbal plant widely appreciated as Chinese medicine. Moreover, it is commonly used as additives in tobacco and food worldwide (Egamberdieva et al 2016). It is also very important for wind hampering, sand fixing, and soil formation in arid and semiarid regions (Li and Wang 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Other reasons are an insufficient number of viable effective bacteria in the rhizosphere that will induce early nodulation under drought [11]. Salinity and drought were previously reported to inhibit the colonization of rhizobia in the rhizosphere of leguminous plants [12,13]. The survival of the rhizobia and the colonization of the plant root are critical for forming nodules and for causing significant effects on plant growth in hostile environments [14].…”
mentioning
confidence: 99%